Redesign Peningkatan Fungsi Mixed Use Area Jalan Jendral Soedirman Kota Salatiga melalui Re-desain Jalur Pedestrian - Alvianto, Puas Andrew; Simanjuntak, Bistok Hasiholan (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023, 2023)
Increasing the Mixed Use Function of the Jendral Soedirman street Area, Salatiga City through Redesigning Pedestrian Pathways . Jendral Sudirman street is Salatiga's busiest business district and economic center. The Jendral Sudirman street business district is used for a variety of purposes, including shopping areas, traditional markets, modern markets, offices, places of worship, hotels, and education. Based on the amount of human movement in the Jendral Sudirman street business area, both by vehicles and pedestrians. However, the area lacks the adequate pedestrian infrastructure to support pedestrian activity. As a result, a review of the pedestrian path's planning and redesign was conducted, taking into account the site's location, materials, and the requirement for facilities and infrastructure. The study used qualitative descriptive method to determine the landscape, planning, and develop a design for the pedestrian path in the Jendral Sudirman street business area using the data obtained through analysis and synthesis. The newly designed tools are powered by Autocad for making siteplan and Google SketchUp for making visual 3D design. The pedestrian redesign of the Jendral Sudirman Road business district is based on the concept of keeping people safe and comfortable. The result indicate that Jendral Sudirman street business area is divided into three zones based on its characteristics, with each zone utilizing andesite stone guiding blocks and pedestrian lamps to increase safety and comfortable for pedestrians and people with disabilities in the night. In terms of comfort, there will be provided shade trees, trash cans, and benches to encourage pedestrian activity on Jenderal Sudirman street.